2016
DOI: 10.3897/jhr.48.6619
|View full text |Cite
|
Sign up to set email alerts
|

Variation of fore wing shape in Melipona mandacaia Smith, 1863 (Hymenoptera, Meliponini) along its geographic range

Abstract: Melipona mandacaia is a stingless bee species responsible for the pollination of many native plants in Brazil, South America. In spite of its ecological and economic importance, natural populations of M. mandacaia have been depleted because of deforestation. In order to evaluate the interpopulation morphometric structure of remaining populations, we carried out geometric morphometric studies based on fore wing shape in this native bee species. The grouping analysis by UPGMA revealed three distinct clusters and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Furthermore, the coefficient of variation of forewing size ranged from 24.1% to 40.7%, indicating relative homogeneity or heterogeneity of the honey bee populations. Overall, the current findings are consistent with the reports of Barour et al (2011) andPrado-Silva et al (2016). In Iraq, Sultan (2015) reported no significant differences in the size and shape of the right front wings of honeybee worker A.mellifera collected from two distinct geographic areas of Baghdad and Diyala.…”
Section: Variations In Wing Size and Shape Among Localitiessupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the coefficient of variation of forewing size ranged from 24.1% to 40.7%, indicating relative homogeneity or heterogeneity of the honey bee populations. Overall, the current findings are consistent with the reports of Barour et al (2011) andPrado-Silva et al (2016). In Iraq, Sultan (2015) reported no significant differences in the size and shape of the right front wings of honeybee worker A.mellifera collected from two distinct geographic areas of Baghdad and Diyala.…”
Section: Variations In Wing Size and Shape Among Localitiessupporting
confidence: 92%
“…In their study, Dolati et al (2013) highlighted that front wing measures discriminated area populations better than hind wing measures using a geometric morphometric method and further reported that populations with small geographical distances had more morphological similarities. Nonetheless, Prado-Silva et al (2016) reported no significant morphometric differences in Melipona mandacaia in relation to altitude, but both fore wing size and shape were correlated to geographic distance.…”
Section: Variations In Wing Size and Shape Among Localitiesmentioning
confidence: 88%
“…Nunes et al (2007), while studying Melipona scutellaris Latreille (Hymenoptera: Apidae), suggested that variation among geographically isolated populations might occur due to the existence of a barrier that prevents frequent migrations of individuals. For example, in bees, wing shape is influenced by geographical distance (Nunes et al 2012, Lima et al 2014, Prado-Silva et al 2016. In a previous study, the relationship between shape and geographical distance was highlighted, suggesting that individuals distributed across different latitudes, longitudes, and altitudes might present differences that are associated with adaptations to local conditions (Berner et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Geometric morphometrics also enables the analysis of correlations between the form and size of structures and the patterns of distribution of individuals across various geographical areas as well as with the patterns of diversification of their life histories. As morphometric variations among insect populations are generally associated with differences in geographical and environmental variables, this methodology has proved to be very useful in this group of organisms (Nunes et al 2012, Romero et al 2014, Prado-Silva et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies verified the efficacy of morphological characters in males to identify morphotypes and cryptic species of the genus Euglossa (Francoy et al, 2012;Quezada-Euán et al, 2015), demonstrating the importance of using males in morphometric studies. Geometric morphometrics, the study of shape and size associated with random factors (Monteiro & Reis, 1999;Klingenberg, 2015), has been used as a tool for studies on intra and interpopulation variation in social bees species (Mendes et al, 2007;Prado-Silva et al, 2016;Combey et al, 2018) and solitary bees (Ferreira et al, 2011;Neves et al, 2012;Dellicour et al, 2017;Grassi-Sella et al, 2018). Such studies have shown the efficacy of that technique on understanding phenotypic expression of these insect populations associated to different environmental factors, such as altitude, geographic distribution, vegetation type and habitat fragmentation.…”
mentioning
confidence: 99%